2019
DOI: 10.1007/s12282-019-00969-0
|View full text |Cite
|
Sign up to set email alerts
|

Predicting metastasis in clinically negative axillary lymph nodes with minimum apparent diffusion coefficient value in luminal A-like breast cancer

Abstract: Background: We investigated the usefulness of the minimum ADC value of primary breast lesions for predicting axillary lymph node (LN) status in luminal Alike breast cancers with clinically negative nodes in comparison with the mean ADC. Methods: Forty-four luminal Alike breast cancers without axillary LN metastasis at preoperative clinical evaluation, surgically resected with sentinel LN biopsy, were retrospectively studied. Mean and minimum ADC values of each lesion were measured and statistically compared be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Investigators found ADC value of LNs was unable to differentiate benign LNs from malignant LNs [ 20 , 21 ]. However, several reports showed that the ADC value of breast lesions in patients with positive axillary LN metastasis was significantly lower than those with negative axillary LNM [ 22 ]. Therefore, our study focused on the ADC value of EC primary lesion in different LN states and found that ADC value showed inverse correlation with PLNM.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators found ADC value of LNs was unable to differentiate benign LNs from malignant LNs [ 20 , 21 ]. However, several reports showed that the ADC value of breast lesions in patients with positive axillary LN metastasis was significantly lower than those with negative axillary LNM [ 22 ]. Therefore, our study focused on the ADC value of EC primary lesion in different LN states and found that ADC value showed inverse correlation with PLNM.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have investigated the diagnostical role of 18F-FDG and ADC for determining tumor aggressiveness in different cancers [32,[37][38][39][40][41][42], none of the studies have compared the efficacy of different PET/MRI imaging biomarkers in HNC tumor aggressiveness prediction. Thus, to our knowledge, this is the first study to compare PET/MRI system-derived imaging parameters in lymph node involvement in HNC.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the Washout median was higher than in patients with NTNBC, indicating that MRI multiparametric imaging is useful for typing prediction of breast cancer. Nonetheless, the literature reveals lower ADC values in patients with TNBC than in patients with NTNBC (30). The differences between the findings may be related to b-value selection, field strength size, ROI outlining method, and so on.…”
Section: Discussionmentioning
confidence: 99%